Glycated haemoglobin, diabetes, and mortality in men in Norfolk cohort of European Prospective Investigation of Cancer and Nutrition (EPIC-Norfolk) - Khaw, Kay-Tee (BMJ, 2001)
OBJECTIVE: To examine the value of glycated haemoglobin (HbA(1c)) concentration, a marker of blood glucose concentration, as a predictor of death from cardiovascular and all causes in men. DESIGN: Prospective population study. SETTING: Norfolk cohort of European Prospective Investigation into Cancer and Nutrition (EPIC-Norfolk). SUBJECTS: 4662 men aged 45-79 years who had had glycated haemoglobin measured at the baseline survey in 1995-7 who were followed up to December 1999. MAIN OUTCOME MEASURES: Mortality from all causes, cardiovascular disease, ischaemic heart disease, and other causes. RESULTS: Men with known diabetes had increased mortality from all causes, cardiovascular disease, and ischaemic disease (relative risks 2.2, 3.3, and 4.2, respectively, P <0.001 independent of age and other risk factors) compared with men without known diabetes. The increased risk of death among men with diabetes was largely explained by HbA(1c) concentration. HbA(1c) was continuously related to subsequent all cause, cardiovascular, and ischaemic heart disease mortality through the whole population distribution, with lowest rates in those with HbA(1c) concentrations below 5%. An increase of 1% in HbA(1c) was associated with a 28% (P<0.002) increase in risk of death independent of age, blood pressure, serum cholesterol, body mass index, and cigarette smoking habit; this effect remained (relative risk 1.46, P=0.05 adjusted for age and risk factors) after men with known diabetes, a HbA(1c) concentration ⩾7%, or history of myocardial infarction or stroke were excluded. 18% of the population excess mortality risk associated with a HbA(1c) concentration ⩾5% occurred in men with diabetes, but 82% occurred in men with concentrations of 5%-6.9% (the majority of the population). CONCLUSIONS: Glycated haemoglobin concentration seems to explain most of the excess mortality risk of diabetes in men and to be a continuous risk factor through the whole population distribution. Preventive efforts need to consider not just those with established diabetes but whether it is possible to reduce the population distribution of HbA(1c) through behavioural means.